Virtopsy: Development and Application in Forensic Practice - Dong-Hua Zou; Yuan-Yuan Liu; Ning-Guo Liu; Yi-Jiu Chen (Journal of Forensic Science and Medicine)
Although represents traditional and classical examination in forensic medicine, nowadays, autopsy, sometimes, is still rejected or not tolerated for its damage to the corpse. Virtopsy offers a noninvasive investigation approach and can also reflect fracture, soft-tissue injury, wound track, and organ trauma objectively and accurately. In addition, virtual autopsies can be used as a complementary tool for areas that are difficult or complex to dissect; in certain cases, where the destruction of a body is prohibited, virtual autopsies provide an alternative to traditional autopsies as an examination method. The virtual autopsy can scan and record a body from head to toe in a short, quick operation, which greatly improves the efficiency of forensic identification. On the other hand, the virtual autopsy is permanently stored through DICOM data and can be subject to a variety of postprocessing operations. Virtual autopsy provides two-dimensional and three-dimensional postprocessing techniques, combining surface and in vivo information with geometrically realistic records, and even combining with finite elements for computer-simulated dynamic simulation studies. Thus, virtopsy can provide visual and powerful evidence for forensic pathological practice. This article mainly synthesizes the latest literature and reviews the application of virtopsy in forensic trauma identification, mechanical asphyxia, drowning, hypothermia and hyperthermia, disease diagnosis, as well as a new research direction of finite element method applied in trauma investigation.